2020
DOI: 10.1016/j.ccell.2020.03.022
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα and GATA-2 Mutations Induce Bilineage Acute Erythroid Leukemia through Transformation of a Neomorphic Neutrophil-Erythroid Progenitor

Abstract: Highlights d Biallelic C/EBPa and GATA-2 ZnF1 mutations synergize during leukemogenesis d GATA-2 ZnF1 mutation generates an erythroid-permissive chromatin state d C/EBPa and GATA-2 mutant NMPs show ectopic erythroid lineage potential d Transformed leukemic NMPs are bipotent neutrophilerythroid leukemia-initiating cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 73 publications
5
40
0
Order By: Relevance
“…A recent report showed that biallelic CEBPA mutation combined with heterozygous mutation in GATA2 induce EL in mice. 50 In these mutant mice, myeloid progenitors, which ectopically expressed erythroid TFs including GATA1, underwent malignant transformation. Thus, during EL development, disrupted balance of lineage TFs (possibly induced by LSD1) may trigger metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that biallelic CEBPA mutation combined with heterozygous mutation in GATA2 induce EL in mice. 50 In these mutant mice, myeloid progenitors, which ectopically expressed erythroid TFs including GATA1, underwent malignant transformation. Thus, during EL development, disrupted balance of lineage TFs (possibly induced by LSD1) may trigger metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…This erythroidpermissive chromatin conformation is retained in bilineage LICs. These results demonstrate that synergistic transcriptional and epigenetic reprogramming by leukemiainitiating mutations can generate neomorphic pre-leukemic progenitors, defining the lineage identity of the resulting leukemia [32].…”
Section: Discussionmentioning
confidence: 72%
“… 17 , 19 A recent mouse model demonstrated that bi-allelic Cebpa mutations led to myeloid leukemia development and that an additional Gata2 mutation enhanced leukemogenesis with a subset of triple transgenic mice (40%) developing leukemia with erythroid and myeloid features. 101 Interestingly, the identified leukemia-initiating cells in both models were neutrophil-monocyte progenitors and molecular characterization of this population revealed distinct function of each cooperating mutations. While bi-allelic Cepba mutations increased expression of erythroid genes, the Gata2 mutation increased chromatin accessibility at erythroid TF motifs (eg, GATA1, ZFPM1, and KLF1) and decreased it at myeloid TF motifs.…”
Section: From Tumor Viruses To Rationale Erythroleukemia Modelsmentioning
confidence: 97%
“…This idea is supported by the recent model combining bi-allelic Cebpa and Gata2 mutations. 101 Hereby, Cebpa and Gata2 mutations synergize by increasing erythroid transcription factor ( Gata1, Klf1, and Zfmp1 ) expression and erythroid chromatin access, respectively, thereby installing ectopic erythroid potential. In addition, while bi-allelic Cebpa mutation resulted in increased erythroid transcription factors expression, it also led to increased expression of several erythroid repressors including Gata2 , Erg , or Cbfa2t3 .…”
Section: Emerging Molecular Mechanism Of Erythroleukemiamentioning
confidence: 99%